"B" Is For Burglar - Grafton, Sue (New York Bantam Books, 1994)
Private investigator Kinsey Millhone digs into a missing- person case, but it soon looks more like a murder when the $12,000 lynx coat in which the wealthy widow in question disappeared shows up again without her.
Keywords: Detective and mystery stories -- Millhone, Kinsey (Fictitious character)